Analysis Effectiveness of Implementation Assessment as Learning on Metacognitive Skills - Aisyah Vynkarini Daniar; Nuniek Herdyastuti; Achmad Lutfi (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This study aims to determine the most effective application of assessment in improving metacognitive skills in the learning process. Method: The method used is a literature review. A literature review is defined as an investigation of scientific articles, books, and other sources related to a particular problem, field of research, or theory to provide an overview, summary, and evaluation of scientific work. This research method uses several steps, including (1) topic identification about Assessment as Learning and metacognitive skill; (2) search and select appropriate articles by Scopus and Google Scholar; (3) analyze and synthesize literature; and (4) text organization. Results: Assessment as learning can be applied using self-assessment, peer assessment, making portfolios and rubrics, as well as group discussions and the teacher. This approach can also be designed online or offline. Self-assessment and peer assessment are more effective in improving metacognitive skills in learning. Novelty: This study can provide an overview assessment design by actively involving learners to improve metacognitive skills, which can help realize the achievement of learning objectives.